Probability and random processes for electrical and computer engineers - Gubner, John A. (New York ; Cambridge : Cambridge University Press., 2006)
The theory of probability is a powerful tool that helps electrical and computer engineers to explain, model, analyze, and design the technology they develop. The text begins at the advanced undergraduate level, assuming only a modest knowledge of probability, and progresses through more complex topics mastered at graduate level. The first five chapters cover the basics of probability and both discrete and continuous random variables. The later chapters have a more specialized coverage, including random vectors, Gaussian random vectors, random processes, Markov Chains, and convergence. Describing tools and results that are used extensively in the field, this is more than a textbook; it is also a reference for researchers working in communications, signal processing, and computer network traffic analysis. With over 300 worked examples, some 800 homework problems, and sections for exam preparation, this is an essential companion for advanced undergraduate and graduate students. Further resources for this title, including solutions (for Instructors only), are available online at www.cambridge.org/9780521864701.
Preface -- 1. Introduction to probability -- 2. Introduction to discrete random variables -- 3. More about discrete random variables -- 4. Continuous random variables -- 5. Cumulative distribution functions and their applications -- 6. Statistics -- 7. Bivariate random variables -- 8. Introduction to random vectors -- 9. Gaussian random vectors -- 10. Introduction to random processes -- 11. Advanced concepts in random processes -- 12. Introduction to Markov chains -- 13. Mean convergence and applications -- 14. Other modes of convergence -- 15. Self similarity and long-range dependence -- Bibliography -- Index.
Text on lining papers.
Includes bibliography and index.
1
Keywords: CIT; Probabilities; Stochastic processes; Electric engineering -- Mathematics; Computer engineering -- Mathematics